Implementación de un plan piloto con flota de carguío de 3.5m3 y acarreo de 15 m3 de capacidad para mejorar el blending de minerales con oro y reducir los costos de operación en la planta de Gold Mill - Minera Yanacocha 2018. - Yspilco de la Cruz, Juan Amerito (2019)
In Minera Yanacocha for the gold mill plant, minerals are extracted from the Tapado and Yanacocha pits; but if the extraction of ore with Au has been deepened, the greater amount of Cu is also being obtained, producing a high variability in its law, the operation costs have increased due to the increase of inputs (Cyanide and lime) and the decrease Percentage in the recovery of the Au. This is the problem of the sum of the trucks that are used for the process are part of the giant fleet CAT 785 with capacity of 150 MT, which generates a mixture of thickened mineral discharge with high Cu content in the Hopper The discharge of the gold mill, so that an optimal mix has not been made, has also taken into account the entry of ore with high variability in the Cu law. In order to improve the problem, they are presented as hypothesis and a pilot plan with a 3.5m3 loading fleet and a 15 m3 capacity haulage can improve the mixture of minerals with gold and the cost of the operation in the plant. Gold Mill The methodology in this thesis used field data, such as reports on CuCN laws and gold recovery, to see the variations in gold recovery using statistical techniques of central tendency. The cost of the loading and hauling equipment is also indicated with the giant and small fleet, to compare the costs in both fleets for a daily production of 15,000 MT / day. It is concluded that the change of the giant fleet by the fleet in the loading and hauling in the gold mill plant should be implemented, as well as the better homogeneity in the gold recovery and the unit cost in this operation.